Analisis Transisi PSAK 109 ke PSAK 409: Implikasi Purifikasi Standar dan Diskresi Manajerial terhadap Saldo Dana Amil BAZNAS RI - Taufik Akbar; Siti Mabrur Rachmah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The implementation of PSAK 409 introduces a new paradigm through the concept of standard purification, which removes rigid administrative constraints in zakat accounting. This study aims to evaluate the impact of the transition from PSAK 109 to PSAK 409 on the structure of amil fund balances at BAZNAS RI for the 2023-2024 period. Using a qualitative descriptive-comparative method from an agency theory perspective, this research dissects the mechanism of operational expense reclassification. The results show that the recovery of the amil fund balance from negative to positive in 2024 was driven by a lump-sum allocation of IDR 39,000,000,000 to the Institutional Strengthening post within the Fisabilillah category. The principle-based flexibility in PSAK 409 provides space for managerial discretion to reclassify expenses to improve the performance of amil fund balances. The absence of real transaction details in this post indicates information asymmetry that potentially reduces public accountability. This study suggests the need for stricter disclosure standards to ensure transparency in the use of zakat funds for internal institutional strengthening.